Pengaruh Intellectual Capital, Struktur Modal, Konservatisme Akuntansi Dan Investment Opportunity Set Terhadap Kualitas Laba - Luh Ayu Erika Safitri; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2023)
The stability of a company's bottom line can be gauged by the caliber of its profits. The purpose of this analysis is to examine how Intellectual Capital, Capital Structure, Accounting Conservativeness, Investment Opportunity, and Profit Quality are related to one another (An empirical study on several manufacturing company listed on Indonesian Stock Exchange Market in 2018-2021). Companies' financial reports served as the secondary data source for this qualitative study. Purposive sampling is used to select 58 businesses over the course of the last four years for this study. In order to analyze the data, this study makes use of multiple regressive linear analysis with SPSS validation. This research shows that the quality of profits is not significantly affected by intellectual capital. Yet, the quality of profits is not significantly affected capital structure. Accounting conservatism has a positive and significant effect on profit quality. Quality of profits is significantly and adversely affected by the investment opportunity set.